Premio Casa de las Américas a Rodolfo Santana - KUDPS, KUDPS (Latin American Theatre Review, 2003)
realm of public opinion in Argentina. The essay is intended to contribute to the study of the mutual influence of aesthetic and political categories, a phenomena that, according to the author, is the most salient trait of cultural production in the westernized world. (HL, in Spanish)